ANALYSIS OF LAND SUBSIDENCE SOURCE MODELING ON SIDOARJO HOT MUD ERUPTIONS - Achmad Fauzi - Nim: 15114027, Arizal
One of the disaster in Sidoarjo region is an eruption of material from beneath the earth in the form of gas and hot mud that occurred in Porong on 29 May 2006. The mudflow disaster caused changes in land formation either horizontally or vertically in the hot mudflow vicinity. This phenomenon is a serious threat because it has a major impact for the people living around the area both socially, environmentally and economically. This research is aimed to analyze the cause of deformation in Sidoarjo hot mudflow area through the mechanism of deformation modeling. This research focused to search the source causing vertical deformation or land subsidence. The land subsidence model that is possible to cause land subsidence in the Sidoarjo hot mudflow area is a deformation model of loading by erupted mud, shrinking of mud conduit and volume loss at depth. To obtain an ideal model, statistical calculations were carried out through the suitability test of Goodness of Fit Test (GOFT) and Root Mean Square Error (RMSE) by using GPS observation data in 2007, 2008, and 2010 as comparative data. Based on the result of the research, the ideal land subsidence model in 2007 with parameters as follows: the volume of mud parameter in surface is 3.7 x 107 m3 for loading by erupted mud model, the radius of conduit is 60 meters for the shrinking of model mud conduit and radius source pressure of 1000 meters for volume loss model at depth. The area less than 1000 meters from the center of the eruption is dominated by the effects of the loading by erupted mud model and the shrinking of mud conduit model while the area over 1000 meters from the center of the eruption is dominated by the effect of the volume loss at depth model.